Comparison of Transabdominal and Transvaginal Sonograms in Evaluation of Cervical Length During Pregnancy. (September 2021) - Fitzpatrick, Anna; DiGiacinto, Dora
Objective: A short cervix during pregnancy indicates a higher risk of preterm delivery. Transvaginal sonography is widely used for the detection of a short cervix. The literature indicates that 21–24 weeks is the most sensitive gestational age to assess transvaginal cervical length (TV CL) of ≤2.5 cm for potential preterm delivery. Pregnancies between 18 and 20 weeks' gestation are generally performed transabdominally; thus, it could be beneficial to have a recognized correlation between the transabdominal cervical length (TA CL) measurement and the TV CL measurement at this earlier time period. Materials and Methods: An online database search produced 13 research articles to be reviewed. Inclusion criteria consisted of TA CL and TV CL assessment of singleton pregnancies with intact membranes. Results: Findings indicate high diagnostic yield when a TA CL of <2.9 cm or TV CL of <2.5 cm is used for defining a shortened cervix when measured between 18 and 20 weeks' gestation. Conclusion: This review of the literature indicates a correlation between average TA CL and average TV CL measurements, although the relationship widens as CLs become shorter.